2019
DOI: 10.1111/nph.16298
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐mediated effects of elevated CO2 and rice cultivars on soil carbon dynamics in a paddy soil

Abstract: Summary Soil organic carbon (SOC) sequestration under elevated CO2 concentration (eCO2) is a function of carbon (C) input and C retention. Nitrogen (N) limitation in natural ecosystems can constrain plant responses to eCO2 and their subsequent effects on SOC, but the effect of eCO2 on SOC in N‐enriched agroecosystems with cultivars highly responsive to eCO2 is largely unknown. We reported results of SOC dynamics from a field free‐air CO2 enrichment experiment with two rice cultivars having distinct photosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 91 publications
1
4
0
Order By: Relevance
“…Our previous study also observed an increase of MBC by 2.1-fold under eCO 2 in the maize season in 2018 [47]. In this study, the increasing percentage of labile organic C components under eCO 2 was relatively lower than other studies [74,76], which could be linked to lower soil moisture regimes. It has been reported that higher DOC and MBC contents occurred at greater soil moisture [77,78], while in the present study, soil moisture was low, and most of the time, soil WFPS was below 40% (Figure 2c).…”
Section: Changes Of Soil Labial Organic C Components and Mineral N Un...supporting
confidence: 50%
See 1 more Smart Citation
“…Our previous study also observed an increase of MBC by 2.1-fold under eCO 2 in the maize season in 2018 [47]. In this study, the increasing percentage of labile organic C components under eCO 2 was relatively lower than other studies [74,76], which could be linked to lower soil moisture regimes. It has been reported that higher DOC and MBC contents occurred at greater soil moisture [77,78], while in the present study, soil moisture was low, and most of the time, soil WFPS was below 40% (Figure 2c).…”
Section: Changes Of Soil Labial Organic C Components and Mineral N Un...supporting
confidence: 50%
“…This could be explained by some studies [10,73], which reported that eCO2 tended to enhance below-ground C allocation, including root exudation and root biomass, which stimulated microbial activities (e.g., the increases in BG activity (Figure 5a)) and soil organic matter decomposition due to priming effects. Hu et al [74] also reported that eCO2 significantly increased the DOC content by 23% and increased the MBC content by 15%. In our study, the presence of soil labile C components in CN plots was significantly higher than that in ZN plots (Figure 3), which might be due to the enhancement in rhizodeposition and microbial growth under N fertilization [8,75].…”
Section: Changes Of Soil Labial Organic C Components and Mineral N Un...mentioning
confidence: 92%
“…(2008) and Hu et al. (2020) found significant increases in root biomass under ECO2 in supplementary studies on other seasons/years at the Wuxi and Jiangdu sites. Such higher root growth may provide C supply source for heterotrophic processes such as denitrification or fungal co‐denitrification and associated N 2 O fluxes (Kammann et al., 2008), while on the other hand increased belowground C may increase microbial demand for inorganic N, and thus, resulting in a temporary immobilization of soil N (Hungate et al., 1999) and a reduction of N 2 O emissions.…”
Section: Discussionmentioning
confidence: 90%
“…However, this increase in non‐CO 2 GHG emissions from rice systems under ECO2 can be significantly reduced by improving water regimes and using alternative fertilization practices such as alternate wetting and drying irrigation schemes, ground cover rice production system and urea deep placement (Beach et al., 2008; Linquist et al., 2015; Yao, Zheng, Liu, et al, 2017; Yao, Zheng, Zhang, et al, 2017). Also, adopting rice cultivars with potentially strong responses to ECO2 may eventually not only improve crop yield but also enhance soil C sequestration (Hu et al., 2020), thereby curbing the future growth of greenhouse effect contributed by rice systems.…”
Section: Discussionmentioning
confidence: 99%
“…As, CO 2 and N are potentially involved in production of more tillers and rice biomass (Fan et al, 2016;Yu et al, 2022). However, in some previous findings the elevated CO 2 also stimulate CH 4 and N 2 O emission along with high yield in some breeding cultivars (Liu et al, 2018;Hu et al, 2020).…”
Section: Relationship Of Excessive Co 2 With Reduced Ch 4 and N 2 O E...mentioning
confidence: 93%